MEANING, MOBILIZATION AND LEARNING: STUDENT'S RELATIONS TO MARTIAL ARTS KNOWLEDGE IN PHYSICAL EDUCATION CLASSES - So, Marcos Roberto; Betti, Mauro [UNESP] (Univ Fed Rio Grande Do Sul, Escola Educ Fisica, 2018)
Based on ''relationship-to-knowledge theory. the purpose of this study is to understand how students relate to martial arts knowledge at Physical Education classes. It is a case study which used interviews with students and a teacher. and classroom observations. Results indicate that identity and socials relations conditioned students' initial impressions and interest towards martial arts. and teaching strategies conditioned mobilization or demobilization toward learning. Martial arts teaching in schools was found to be dominated by tensions. Student's preconceptions have to be re-framed; the teacher has to (re)construct pedagogical knowledge on that content; and Physical Education as a school subject should interrelate all the learning figures: object-knowledge. domain-knowledge and relational-knowledge.
Keywords: Martial arts; Knowledge; Students